Gender, globalisation and empowerment: a study of women who work in Sri Lanka's Export Processing Zones. (1st April 2012) - ,; ,; ,
Abstract : This paper provides new insights into the ways in which women experience formal employment as a result of working in export-oriented factories in a 'developing' nation. It is based on research that was funded by AusAID's Australian Development Research Award and conducted by investigators from Edith Cowan University (ECU) in Australia and the Centre for Research on Women (CENWOR) in Sri Lanka. Between 2008 and 2011, 2, 304 women who worked in factories in Sri Lanka's Export Processing Zones were surveyed. The focus of the study was on gender empowerment and the aim was to collect empirical information on the lived experiences of these women factory workers vis-a-vis gender empowerment. According to neoliberal thinking, such women in a developing country, receiving a regular salary, should be at the forefront of international development and hence the most likely to be empowered. The paper concludes that the evidence is contradictory: these women were simultaneously both empowered and disempowered by the experience of formal employment.